2016
DOI: 10.4236/aid.2016.63014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GeneXpert MTB/RIF Assay in Broncho Alveolar Lavage and Gastric Lavage Samples

Abstract: Objective: To compare the yield from Gastric lavage (GL) and Broncho alveolar lavage (BAL) samples in adult patients suspected case of Tuberculosis but not producing sputum. Methodology: 80 adults with suspected case of tuberculosis but not producing sputum were recruited. 72 patients were then subjected to one gastric lavage followed by Broncho-alveolar lavage in the same morning. The collected samples were subjected to GeneXpert MTB/RIF assay. Result: Of the 72 patients samples, the mean age was 38.6 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Earlier study shows that the GeneXpert for MTB in BAL fluid has been found to be positive in 48.6%. 9 The present study shows that in 25 cases, direct smear was found to be negative, but in GeneXpert was negative cases in 14 cases. This shows that the GeneXpert in BAL plays a vital role in diagnosing TB patients as compared with that of direct smear for MTB in BAL.…”
Section: Methodssupporting
confidence: 40%
“…Earlier study shows that the GeneXpert for MTB in BAL fluid has been found to be positive in 48.6%. 9 The present study shows that in 25 cases, direct smear was found to be negative, but in GeneXpert was negative cases in 14 cases. This shows that the GeneXpert in BAL plays a vital role in diagnosing TB patients as compared with that of direct smear for MTB in BAL.…”
Section: Methodssupporting
confidence: 40%
“…Similarly, another Pakistani study by Mahat R et al also reported the higher positivity of gastric lavage with GXP 38.9%. 17 Another study of Brown M et al from United Kingdom also reported the pulmonary tuberculosis in 43% patients on evaluation of gastric lavage. Researcher also reports higher positivity of gastric lavage with gene culture 30% followed by smear with 13%.…”
Section: Discussionmentioning
confidence: 95%